2018
DOI: 10.7150/jca.27579
|View full text |Cite
|
Sign up to set email alerts
|

A nomogram to predict long-time survival for patients with M1 diseases of esophageal cancer

Abstract: Objective: To evaluate the clinicopathologic characteristics of the long-time survivals and construct a clinical nomogram using the Surveilance, Epidemiology, and End Results (SEER) database.Materials and Methods: Information of patients diagnosed with M1 stage esophageal cancer from 2010-2014 was retrieved from SEER database. Patients with unknown information of AJCC TNM stage or metastatic sites or marital status or surgery or survival were excluded. Demographic and clinicopathologic characteristics were com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
14
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 15 publications
3
14
0
Order By: Relevance
“…In breast cancer, patients with BMs have significantly better survival than those who have metastases to other sites (20). On the other hand, OS is significantly worse in patients with EC with BMs compared to those with metastases to other sites (9,21). In the current study, the median OS from the time of BM diagnosis in patients with EC was five months, which is consistent with previous reports of 2–4 months (9,22).…”
Section: Discussionmentioning
confidence: 96%
“…In breast cancer, patients with BMs have significantly better survival than those who have metastases to other sites (20). On the other hand, OS is significantly worse in patients with EC with BMs compared to those with metastases to other sites (9,21). In the current study, the median OS from the time of BM diagnosis in patients with EC was five months, which is consistent with previous reports of 2–4 months (9,22).…”
Section: Discussionmentioning
confidence: 96%
“…A greater number of metastatic organs was related to worse prognosis. In spite of the indolent nature of oligometastatic EC, the large number of metastatic organs represents the higher growth potential and higher ability to metastasize, which could result in widespread metastasis and poor prognosis 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Global alterations of miRNA and mRNA expression are involved in the regulatory mechanisms of the development and progression of ESCC. [57] Through PPI analyses, we found that the 13 mRNAs that were assessed as hub genes might play crucial roles in ESCC. Matrix metalloproteinases (MMPs) are strongly expressed in the cytoplasm of cancer cells, especially in the invasive margin, and are weakly expressed in stromal cells.…”
Section: Discussionmentioning
confidence: 99%